Impact of Remittance, Money Supply and Inflation on Economic Growth of Nepal: Using Autoregressive Distributed Lag Model (ARDL) - Upadhyay, Hari Prasad; Pradhan, Bijay Lal; Poudel, Omkar; Sapkota, Keshab Raj; Simkhada, Daya Ram (BMC Journal of Scientific Research, 2022)
Remittances have become a major source of funding in developing countries. A time series analysis was conducted by taking the 25 years data of economic growth as a dependent variable while remittance, money supply and Inflation as independent variables form the annual report of Economic survey of Nepal (2020/21). The autoregressive distributive lag (ARDL) was used to study the relationship among the variables. The trend of economic growth and total percentage of economic growth is in increasing order. The relation between then was found as LN(Economic Growth) =8.0740 +0.220*LNREM + 0.3123 *LNM2-0.0802*LNINF. The stability test of long-run coefficient including short run was studied using ARDL model and are confirmed using Cumulative Sum chart (CUSUM) and cumulative sum of squares test (CUSUMSQ) test. Finding shows that there is long run positive relationship between remittance, money supply, inflation on economic growth of Nepal. From the analysis it is clear that coefficients of error correction are highly significant this indicate that adjustment to longterm equilibrium in the dynamic model and ARDL model showed all the independent variables had positive impact on economic growth of Nepal.